MANAGEMENT IN THE TURKESTAN AS IN THE FIRST YEARS OF THE FORMATION OF SOVIET POWER - Саипова К. Д. (TARIXIY TADQIQOTLAR, 2025)
In this article, the author, on the basis of archival materials, put forward the issue of managing the political, economic and cultural life of the peoples in the TASSR in the first years of the establishment of Soviet power.